The preemption war : when federal bureaucracies trump local juries - McGarity, Thomas O. (Yale University Press, 2008)
Most people are unaware of a quiet war that has been raging for the last decade in the courts, federal regulatory agencies, and Congress8212;a war over federal agency preemption of state common law claims. But the outcome of these battles will affect us all, says regulatory law expert Thomas O. McGarity, and consumers stand to be the biggest losers. In this comprehensive and balanced book, McGarity takes up for the first time this increasingly important subject. He shows how preemption affects the way citizens are protected from harm and companies are held accountable for damage they unlawfully cause. € The book offers scholars and policymakers a full analysis of the legal and policy issues under debate, and it brings into sharp focus the impact of preemption on the lives of people involved in actual lawsuits. McGarity highlights the arguments for and against preemption and suggests guidelines for resolving difficult issues in a variety of contexts.